The study of employability skills levels among Islamic banking students - Omar, Noor Hazimah; Mazlan, Noor Hairul Azmil; Hashim, Noor Hasmahan (2015)
The aim of study was to analyze "The level of employability skills among Islamic Banking Student". The study was conducted and focus on respondents which is the final year students, Islamic Banking and Finance Universiti Malaysia Kelantan. 83 of questionnaire were distributed to 83 respondents. The research methodology method is quantitative that used to have the better result. In order to analyze data, statistic package (SPSS) was used in this study. The result showed that "The level of employability skills among Islamic Banking Student" are in the moderate level.